Osteochondral Injury, Management and Tissue Engineering Approaches - Jacob, George; Shimomura, Kazunori; Nakamura, Norimasa (Frontiers in Cell and Developmental Biology, 2020)
Osteochondral lesions have been a common clinical problem for orthopaedic surgeons worldwide and are associated with various clinical scenarios ranging from trauma to osteonecrosis. The lesions differ from chondral lesions as they involve the subchondral bone and chondral surface, making their management more complex than an isolated chondral injury. Subchondral bone involvement allows for a natural healing response from the body as marrow elements can come into contact with the defect site. However, this repair is inadequate resulting in fibrous scar tissue. The second differentiating feature of osteochondral lesions is that damage to the subchondral bone has deleterious effects on the mechanical strength and nutritive capabilities to the chondral joint surface. The clinical solution must, therefore, address both the articular cartilage as well as the subchondral bone beneath it to restore and preserve joint health. Both cartilage and subchondral bone have distinctive functional requirements and therefore their physical and biological characteristics are very much dissimilar, yet they must function together as one unit to meet the requirements of the joint surface. In the past the obvious solution was autologous graft transfer, where an osteochondral bone plug was harvested from a non-weight bearing portion of the joint and implanted into the defect site. Allografts have been utilized similarly to eliminate the donor site morbidity associated with autologous techniques and overall results have been good but both techniques have their drawbacks and limitations. Tissue engineering has thus been an attractive option to create multiphasic scaffolds and implants. Biphasic and triphasic implants have been under study which have both a chondral and subchondral component with an interface between the two to provide an implant which is biocompatible and emulates the osteochondral unit as a whole. It has been challenging to develop these implants and many manufacturing techniques have been used to bring together two unalike materials and combine them with cellular therapies. We summarize the functions of the osteochondral unit and describe the currently available management techniques under study.